Thermal Processes Using Attosecond Laser Pulses When Time Matters - Kozlowski, Miroslaw; Marciak-Kozlowska, Janina (Springer Series in Optical Sciences,, 2006)
This book contains a study of the thermal processes initiated by attosecond laser pulses. Considering the existence of the experimental evidence for the trains of the attosecond laser pulses, we developed the theoretical framework for attophysics, i.e. physics of phenomena with time duration in the attosecond domain. This time domain is concerned with phenomena whose duration is much shorter than the relaxation time for atomic, molecular and nanoparticles scales.